Expression of HER-2/neu, epidermal growth factor receptor, vascular endothelial growth factor, cyclooxygenase-2, estrogen receptor, and progesterone receptor in small cell and large cell neuroendocrine carcinoma of the uterine cervix: a clinicopathologic and prognostic study. Issue 4 (1st June 2005) - Tangjitgamol, S.; Ramirez, P. T.; Sun, C. C.; See, H. T.; Jhingran, A.; Kavanagh, J. J.; Deavers, M. T.
Abstract : We studied the immunohistochemical expression of HER-2/neu, epidermal growth factor receptor (EGFR), vascular endothelial growth factor (VEGF), cyclooxygenase-2 (COX-2), estrogen receptor (ER), and progesterone receptor (PR) in uterine cervical small cell and large cell neuroendocrine carcinomas (SCNECs and LCNECs) from 24 patients seen at The University of Texas M.D. Anderson Cancer Center. The objectives were to determine their expression and prognostic role in survival. Twenty-three cases (95.8%) expressed VEGF. The tumors expressing EGFR, HER-2/neu, and COX-2 were modest in numbers: eight (33.3%), 10 (41.7%), and seven (29.2%), respectively. Only one tumor (4.2%) expressed ER, and only two tumors (8.3%) expressed PR. No significant differences in the expression of these factors were found between SCNECs and LCNECs or between stage I and stage II–III tumors. The median overall survival was 21.1 months (95% confidence interval [CI], 17.2–25.0 months). Only HER-2/neu expression was significantly associated with survival. Patients with negative HER-2/neu expression tumors had significantly shorter survival than those whose tumors were positive, 14.2 months (95% CI, 10.6−17.7 months) versus 33.1 months (95% CI, 0−76.92 months) ( P = 0.03). There was a trend toward worse survival in patients with EGFR expression, but this finding was not significant. The combination of negative HER-2/neu expression and positive EGFR expression had the worst impact on survival.